“I Am Not Mujer Metralleta, I Am Marcela Rodríguez’. Representations of Womens’ Militancy in Armed Organizations (Chile, 1983-1990); [“Yo No Soy la Mujer Metralleta, Soy Marcela Rodríguez”. Representaciones de la Militancia de Mujeres en el Mapu-Lautaro (Chile, 1983-1990)] - Acevedo-Arriaza, N (Universidad Nacional de Rosario - Facultad de Humanidades y Artes, Escuela de Historia, 2025)
The following article analyzes the representations surrounding the figure of Marcela Rodríguez, referred to by the press during the military dictatorship as the "machine gun woman." My hypothesis is that while this press criminalized women in leftist armed organizations, objectifying their bodies and political actions, as was the case with Marcela Rodríguez, a member of MAPU-Lautaro. At the same time, this organization used the representation of the "Subversive Woman" to strengthen its policy regarding everyday rights and demonstrate that gender conflicts did not exist within it. Finally, Marcela Rodríguez s memoirs allow for an analysis of women s participation in these organizations, but at the same time reveal conflicts that militants have not examined in detail. The methodology combines press and document analysis, as well as the memoirs of women who participated in this organization. © 2025 Universidad Nacional de Rosario - Facultad de Humanidades y Artes, Escuela de Historia. All rights reserved.